Empowering the Teaching of Malaysian Indigenous Language via Knowledge Sharing - Alwi, Azwinawati; Mehat, Mazlina; Izza Arshad, Noreen; Mohd Ariffin, Mazeyanti; K. Sugathan, Savita (International Journal of Engineering and Technology, 2018)
It is always a great challenge for a teacher to sustain the interest of the indigenous students and getting to know them by using their language could help. However, very minimal teaching resources are documented and available for the usage of the indigenous language educators. Each educator are knowledgeable about the language and its teaching. By sharing their knowledge over a suitable platform, they could learn from each other on how to sustain the students’ interest and also the language itself. In Malaysia, primary school teachers, who are teaching Bahasa Semai, one of the indigenous languages that exist in Malaysia, could be assisted with computing technology that will allow them to specifically share their knowledge about Bahasa Semai and how to teach it. The purpose of this paper is to highlight the functionalities needed in developing a portal that could assist in teaching Bahasa Semai. Agile development methodology was adopted in developing the portal. Upon completion of the development, potential users, who are Bahasa Semai educators and coordinator were interviewed and they were positively satisfied with the end result. The portal will be available online upon the completion of its second cycle and should be able to give great benefit to educators, students and coordinator.